City Branding - Aveiro: how Aveiro is perceived by its residents and tourists? - Anastácio, Margarida Nunes (2019)
The worldwide tourism development, aligned with the globalization and the competition between places & cities create the need for cities to differentiate themselves from other cities around the world, in order to attract investment, tourists and future residents. City branding is the strategic tool that allows cities to differentiate from one another, by publicizing the city’s competitive advantage. Until the last decade, city branding has not been the subject of much analysis. Derived from the city marketing, the city branding aims to create preference, loyalty to the city and a positive customer-visitor experience among the various targets. This project has conducted interviews to major stakeholders from public and private sectors and has descriptively analysed perceptions of 274 locals / residents and tourists on Aveiro’s characteristics. Finally, we suggested recommendations to be implemented by city administrators and promoters, allowing them to brand the city and to turn Aveiro in one of the tourists first choice when visiting a city. The city of Aveiro, in the Centre of Portugal, known by Ria de Aveiro, the moliceiro, the architecture and the gastronomy, was the chosen city for this study for being one of the tourism destinations in Portugal where the topic of city branding has never been explored. The region of Aveiro is very diverse and dynamic for the tourism activity, being Aveiro the municipality of the region with higher volume of tourism. The main contribution of this study relied on the practical approach and specific recommendations suggested to the city and region.